UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL, FRAKSI POLAR, SEMI POLAR DAN NONPOLAR DAUN SIRIH CINA (PEPEROMIA PELLUCIDA (L.) KUNTH) DENGAN METODE DPPH - Nurliansyah, Nurliansyah; Ridwanto, Ridwanto; Dalimunthe , Gabena Indrayani; Yuniarti , Rafita (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Chinlelsel beltell lelavels (Pelpelromia pelllucida (L.) Kunlth) arel traditionlally useld as a meldicinlel for relducel thel painl of rhelumatism anld gout. Chinlelsel beltell has selconldary meltabolitel compounlds, nlamelly alkaloids, flavonloids, saponlinls, tanlnlinls anld stelroids. activitiels. Thelrel arel anltioxidanlt compounlds that funlctionl as anltidotels anld canl stabilizel frelel radicals. Anltioxidanlts work by protelctinlg againlst damagel causeld by frelel radicals. NLatural anltioxidanlt compounlds arel oftelnl founld inl planlt parts such as lelavels, flowelrs anld fruit. Thel melthod most oftelnl useld to telst thel anltioxidanlt activity of meldicinlal planlts is thel telst melthod usinlg DPPH radicals. This relselarch aims to deltelrminlel thel potelnltial anltioxidanlt activity of elthanlol elxtract anld polar, selmi-polar anld nlonl-polar fractionls of Chinlelsel beltell lelavels (Pelpelromia pelllucida (L.) Kunlth) usinlg thel Dpph melthod. This relselarch inlcludeld macelrationl of Chinlelsel beltell lelavels with 96% melthanlol for 5 days anld relmacelrationl for 2 days. Thel thick elxtract was fractionlateld usinlg nl-helxanlel anld elthyl aceltatel solvelnlts. Thel anltioxidanlt activity telst useld DPPH (1,1-diphelnlyl-2-picrylhydrazyl) by melasurinlg thel anltioxidanlt activity againlst Dpph frelel radicals qualitativelly anld quanltitativelly. Thel relsults of thel anltioxidanlt activity telst of thel Chinlelsel beltell lelaf fractionl usinlg thel dpph melthod havel a velry stronlg catelgory with anl IC50 activity valuel inl thel watelr fractionl of 40.71525µg/ml, thel elthyl aceltatel fractionl has a velry stronlg strelnlgth with a catelgory of 6.17085µg/ml, anld thel nl-Helxanlel fractionl has velry stronlg strelnlgth with a catelgory of 23.8421 µg/ml. Thel selconldary meltabolitel compounlds conltainleld inl Chinlelsel beltell lelavels (Pelpelromia pelllucida (L.) Kunlth) originlatinlg from Meldanl City sub-district arel flavonloids, alkaloids, saponlinls, tanlnlinls, glycosidels anld stelroids/telrpelnloids